Active control of noise in a tube - Zheng, Hong. (2008)
This dissertation focuses on the design and development of a noise control system using the techniques of adaptive signal processing in an air-handling tube. Several adaptive filtering techniques in acoustic path modeling and noise control are investigated through simulations and experiments. Here, we employ modern digital signal processing (DSP) techniques and robust adaptive filtering algorithms to implement active control in low frequency noises.